Assessing facilitated passage and spawning migration patterns of Razorback Suckers, Xyrauchen texanus, in the San Juan River - Bogaard, Matthew R. (Kansas State University, 2021)
In the southwestern United States, decades of water diversions, construction of large impoundments, and loss of floodplain habitats have all contributed to a highly fragmented riverine landscape. River regulation, through damming, alters the magnitude and timing of discharge and temperature regimes and interrupts nutrient and sediment transport. Additionally, barriers negatively affect vital rates of riverine fish populations that rely on connected migratory routes to complete components of their life cycle, such as spawning migrations. A capture-translocation strategy has been implemented for Razorback Suckers, Xyrauchen texanus, in the San Juan River to mitigate negative effects of barriers, while precluding passage of nonnative species. We used active and passive radio telemetry to assess Razorback Sucker movements following translocation upstream of two barriers. Furthermore, we used seven years of Passive Integrated Transponder tag detection data at each barrier to test associations of Razorback Sucker occurrence and environmental parameters that may cue spawning migrations. While translocated individuals tended to return downstream of barriers within a year of passage, our results indicated that most individuals (>80%) remained upstream long enough to successfully spawn. Following translocation at each barrier, we observed upstream movements ranging from 2 to 262 km and detected distinct aggregations within the expected spawning season. Timing of putative spawning migrations had strong associations with water temperature, where the largest proportions of Razorback Suckers were first detected at barriers as mean weekly water temperature was increasing between 7.1 to 14.2 °C. Our research provided a model that managers can use to predict the timing of occurrence of migrating Razorback Suckers, serving as a tool to improve efficiency of selective passage facilities by prioritizing passage efforts during times of peak migration. While translocation provides an option of selective passage that may seasonally reconnect migratory routes for a proportion of the population and increase spawning potential, it is not clear if this will be enough to mitigate other recruitment bottlenecks, (e.g., access to predator-free habitats) necessary to recover Razorback Sucker populations.
Keywords: Razorback Sucker; Radio telemetry; Endangered fish; Movement; San Juan River